Conformal and probabilistic prediction with applications : 5th International Symposium, COPA 2016, Madrid, Spain, April 20-22, 2016, Proceedings /: 5th International Symposium, COPA 2016, Madrid, Spain, April 20-22, 2016, Proceedings. (2016) - Unknown
No abstract available